Pathobiological studies on cultured populations of the freshwater prawn, Macrobrachium rosenbergii (de man, 1879), Margarita Island, Venezuela - Rodríguez, Bethsy; Lodeiros, César; Conroy, Gina; Conroy, David; Graziani, César (Revista Científica de la Facultad de Ciencias Veterinarias, 1970)
Â Studies on the presence of diseases and parasites affecting larvae, post-larvae, juveniles and adults of Macrobrachium rosenbergii, cultured in Margarita Island, Venezuela, were undertaken. The presence of peritrichous colonial ciliates identified as Epistylis and Vorticella spp., and suctorians identified as Acineta and Tokophrya spp., occurring as ectocommensals or epibionts was confirmed. These organisms were encountered on the gills and exoskeleton of the four stages of growth examined. The presence of the cyanophyte algae Anabaena and Lyngbya spp., and the chlorophyte algae Cosmarium and Ulothrix spp., was also detected. Trichomes of filamentous bacteria identified as Leucothrix sp. were encountered in samples of the gills and exoskeleton of post-larvae and adults. Bacteriological studies on larvae from stages II and III, and of the water used for the larvae, revealed the presence of an abundant bacterial flora, in which representatives of the genera Aeromonas, Arthrobacter, Flavobacterium, Moraxella, Pseudomonas and Vibrio were present. A more detailed study of the aeromonads, pseudomonads and vibrios showed that the isolates belonged to the species Aeromonas formicans, Pseudomonas alcaligenes and Vibrio anguillarum, respectively. Fungi imperfecti, identified as Fusarium sp., were detected in specimens of post-larvae and adults, and the organism was successfully isolated from the gills on Sabouraud dextrose agar plates.